PANDANGAN TENTANG APAKAH POLITIK HUKUM ITU? - Asep Bambang Hermanto (Program Magister Ilmu Hukum Universitas Pancasila, 2019)
Law is a very complex entity. The complexity of the law led to the law that can be studied from various viewpoints such as philosophy of law, legal history, anthropology of law, comparative law, and others, are now growing and developing legal politics (politics of law) this is indisputable proof of the truth of the above statement . Each variety of legal disciplines above will not be able to work alone, because actually all are intertwined (related / unrelated) each other. That is the discipline of law does not have any meaning without involving other legal disciplines, including the absence of legal politics. All of them are auxiliary sciences that can be used as an approach or tool of analysis, so that all legal product is made to run effectively. Political law as a discipline that is still young and the law has not yet had an established scientific structures. But the politics of law as one of the compulsory subjects level graduate program in Master of Law by Decree No. Mendikbud 002 / U / 1996 on the prevailing national curriculum.